The Diversity of Gastropod as Bio-Indicator of Contamination of Leachate of Jatibarang Dumping Ground in Kreo River Semarang City - Dinar Mega Ayu; Ary Susatyo Nugroho; Rivanna Citraning Rahmawati (Universitas Sebelas Maret, 2015)
Gastropod is a biotic component which is important in river ecosystem. Gastropod will respond the changes of physical and chemical condition of the river so that it can be the bio-indicator of the contamination. This research is aimed to know the diversity of gastropod as bio-indicator of contamination of leachate of Jatibarang dumping ground in Kreo river Semarang City. This research was conducted on April until June 2015. Gastropod sample was got using purposive sampling using Surber Net. Gastropod sampling was conducted in three station with three sampling spots in each station, physical-chemical factor measurement including temperature, brightness, pH, COD, DO and BOD was also conducted in every station. The analysis of research result showed that diversity index and the number of gastropod decreased in station which was contamined by leachate. The contaminated station was station II. Diversity index was 0,66094 and the number of gastropod was 114 ind/m2. This condition was different compared to station I which had not been contaminated. In station I, diversity index was 1,03255 and the number of gastropod was 175 ind/m2. So was the station which got the recovery, the station III, where diversity index was 0,82691 and the number of gastropod was 140 ind/m2. Statistical analysis result also showed that gastropod diversity correlated strongly to temperature, brightness, pH, COD, DO and BOD on Kreo river. This result showed that gastropod responded the changes of physical-chemical condition of Kreo river which was caused by the contamination of leachate of Jatibarang dumping ground. From the research result, it can be concluded that gastropod diversity on Kreo river can be used as bio-indicator of the contamination of leachate of Jatibarang dumping ground.Keywords: leachate, Jatibarang dumping ground, gastropod, Kreo river